2009
DOI: 10.1086/600143
|View full text |Cite
|
Sign up to set email alerts
|

Does Your Cohort Matter? Measuring Peer Effects in College Achievement

Abstract: We estimate peer effects in college achievement using a dataset in which individuals are exogenously assigned to peer groups of about 30 students with whom they are required to spend the majority of their time interacting. This feature enables us to estimate peer effects that are more comparable to changing the entire cohort of peers. Using this broad peer group, we measure academic peer effects of much larger magnitude than found in previous studies. The effects persist at a diminished rate into follow-on yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
322
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 475 publications
(344 citation statements)
references
References 18 publications
16
322
1
5
Order By: Relevance
“…In the context of post-secondary education, a number of studies address the selection problem by exploiting exogenous assignment of students to sections (Booij et al, 2015;De Giorgi, Pellizzari, & Woolston, 2012), dorm rooms (e.g., Brunello, De Paola, & Scoppa, 2010;Sacerdote, 2001;Zimmerman, 2003) and living communities in military colleges (Carrell et al, 2009;Carrell et al, 2013;Lyle, 2007). Linear-in-mean point estimates in these environments are typically small and positive or statistically insignificant.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of post-secondary education, a number of studies address the selection problem by exploiting exogenous assignment of students to sections (Booij et al, 2015;De Giorgi, Pellizzari, & Woolston, 2012), dorm rooms (e.g., Brunello, De Paola, & Scoppa, 2010;Sacerdote, 2001;Zimmerman, 2003) and living communities in military colleges (Carrell et al, 2009;Carrell et al, 2013;Lyle, 2007). Linear-in-mean point estimates in these environments are typically small and positive or statistically insignificant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Take, for example, adjustment of teachers' behavior as one potential channel of peer effects. While Duflo et al (2011) have shown that this channel matters in Kenyan classrooms, it is irrelevant in the settings where peer groups have no common teachers like in living communities (Carrell et al, 2009;Carrell et al, 2013;Lyle, 2007;Sacerdote, 2001;Zimmerman, 2003). A better understanding of the channels that drive peer effects could lead to a better understanding about why they differ across contexts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First and foremost, a large-scale trial with random assignment of teachers and students to classrooms is extremely difficult to conduct. While there are some interesting cases of large-scale random assignment at the college level (Sacerdote (2001), Carrell et al (2008)) and in foreign countries (Carman and Zhang (2008), Ding and Lehrer (2007), Duflo et al (2008), Lai (2008), the legal and political hurdles to random assignment at the elementary and secondary level in the United States are daunting. As a result, there has been only one large-scale randomized trial in U.S. primary and secondary schools, Tennessee's Student/Teacher Achievement Ratio (STAR) experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The literature uses various strategies to isolate these effects. The research is generally categorised by natural experiments (Boozer and Cacciola, 2001;Sacerdote, 2001;Zimmerman, 2003;Kang, 2007), quasi-experimental (Carrell et al,. 2009;Hoxby;2000), fixed effects (Vigdor and Nechyba, 2004;Hanushek et al,.…”
Section: Existing Literaturementioning
confidence: 99%